Political change and the rise of labour in comparative perspective : Britain and Sweden, 1890-1920 - Hilson, Mary (Nordic Academic ; Gazelle Drake Academic [distributor], 2006)
A comparative analysis of social change, democratization, and the development of modern party politics in Britain and Sweden during the period 18801930, this book presents the similarities of political changes in these two countries at this time and also in the wider European context, with particular reference to the emergence of social democracy as a political current.